2000
DOI: 10.1007/s100960000236
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for Ventilator-Associated Pneumonia in a Multidisciplinary Intensive Care Unit

Abstract: A prospective study was conducted to determine the incidence, risk factors and pathogens of ventilator-associated pneumonia (VAP) in 198 patients requiring mechanical ventilation for more than 48 hours. VAP occurred in 67 (33.8%) patients. Risk factors associated with VAP were admission APACHE II score >20 (odds ratio [OR] 4.77, 95% confidence interval [CI] 2.04-11.27, P<0.001), mechanical ventilation > 10 days (OR 44.4, 95% CI 2.16-26.7, P< 0.0001), ICU length of stay >10 days (OR 9.4, 95% CI 3.55-25.65, P< 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 11 publications
5
30
0
Order By: Relevance
“…aeruginosa , respectively. Similar observations were made by other investigators that reported 96-100% resistance;[1112] whereas, other workers have reported lower rate of resistance (37-67.5%) to ceftazidime. [1113] High rate of resistance at our center might be due to the selective influence of extensive usage of third generation cephalosporins.…”
Section: Discussionsupporting
confidence: 89%
“…aeruginosa , respectively. Similar observations were made by other investigators that reported 96-100% resistance;[1112] whereas, other workers have reported lower rate of resistance (37-67.5%) to ceftazidime. [1113] High rate of resistance at our center might be due to the selective influence of extensive usage of third generation cephalosporins.…”
Section: Discussionsupporting
confidence: 89%
“…Garnacho-Montero et al [96] and Sofianou et al [98] suggested that VAP due to A. baumannii was not associated with a poorer prognosis than other causes of VAP, whereas Weingarten et al [99] suggested that the severity of the illness itself is the major determinant of mortality. In addition, the reported results from the SCOPE project, a prospective study with 49 participating hospitals in the USA, showed that the mortality of 111 patients with A. baumannii bloodstream infections was not significantly different from that of 2952 patients with bacteraemias caused by other Gram-negative organisms [90].…”
Section: The Clinical Impact Of Acinetobacter Infectionsmentioning
confidence: 97%
“…was responsible for 35% of ventilator associated pneumonia (VAP), making it the most conspicuous and dominant pathogen amongst all other bacteria encountered in that study. 17 However, only few case-control studies have identified and systematically reported the various risk factors associated with Acinetobacter infection or colonization. 5,7 Potential risk factors for Acinetobacter infection in many studies were prior surgery or prior use of broad-spectrum antibiotics.…”
Section: Discussionmentioning
confidence: 99%